Evolution of the eccentricity and inclination of low-mass planets subjected to thermal forces: a numerical study - Cornejo, S; Masset, F S; Chametla, R O; Fromenteau, S (arXiv.org, 2023)
By means of three dimensional, high resolution hydrodynamical simulations we study the orbital evolution of weakly eccentric or inclined low-mass protoplanets embedded in gaseous discs subject to thermal diffusion. We consider both non-luminous planets, and planets that also experience the radiative feedback from their own luminosity. We compare our results to previous analytical work, and find that thermal forces (the contribution to the disc's force arising from thermal effects) match those predicted by linear theory within \(\sim 20\)%. When the planet's luminosity exceeds a threshold found to be within \(10\)% of that predicted by linear theory, its eccentricity and inclination grow exponentially, whereas these quantities undergo a strong damping below this threshold. In this regime of low luminosity indeed, thermal diffusion cools the surroundings of the planet and allows gas to accumulate in its vicinity. It is the dynamics of this gas excess that contributes to damp eccentricity and inclination. The damping rates obtained can be up to \(h^{-1}\) times larger than those due to the resonant interaction with the disc, where \(h\) is the disc's aspect ratio. This suggests that models that incorporate planet-disc interactions using well-known formulae based on resonant wave-launching to describe the evolution of eccentricity and inclination underestimate the damping action of the disc on the eccentricity and inclination of low-mass planets by an order of magnitude.